2015
DOI: 10.1016/j.critrevonc.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Biologicals, platelet apoptosis and human diseases: An outlook

Abstract: Platelets, once considered mediators of hemostasis and thrombosis, are now known to be involved in wound healing, inflammation, cardiovascular diseases, diabetes, arthritis, and cancer. Recent reports attest that platelets possess the cellular machinery to undergo apoptosis and that platelet apoptosis can be triggered by myriad stimuli including chemical and physical agonists, and pathophysiological conditions. Augmented rate of platelet apoptosis leads to thrombocytopenia, bleeding disorders and microparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 56 publications
0
31
0
2
Order By: Relevance
“…Among other cells such as endothelial and immune cells, PLTs are able to form PMPs which play a pivotal role in immunology and vascular biology. These particles are thought to be of significant clinical relevance as they can bind to and interact with macrophages, neutrophil granulocytes, and endothelial cells [102,103]. They were first described already in 1967 by Wolf et al [104].…”
Section: Platelet Microparticles (Pmp)mentioning
confidence: 99%
“…Among other cells such as endothelial and immune cells, PLTs are able to form PMPs which play a pivotal role in immunology and vascular biology. These particles are thought to be of significant clinical relevance as they can bind to and interact with macrophages, neutrophil granulocytes, and endothelial cells [102,103]. They were first described already in 1967 by Wolf et al [104].…”
Section: Platelet Microparticles (Pmp)mentioning
confidence: 99%
“…These compounds were able to interfere with blood clotting, most probably via the inhibition of cytochrome oxidase. Tomasiak et al (2004) also proved that impairment of mitochondrial complex III (cytochrome oxidase) by nitric oxide (NO) or mitochondrial complex IV reduced mitochondrial energy production, which in turn inhibited platelet aggregation and secretion, thus demonstrating that platelet-activated coagulation depends on adequate mitochondrial respiratory function.…”
Section: Platelet Function Regulation and Mitochondriamentioning
confidence: 98%
“…Several studies reported on the effects of various compounds to induce platelet apoptosis via the mitochondria pathway. Another chemotherapeutic drug, cisplatin, increased ROS production, induced the mitochondrial translocation of the proapoptotic Bax with subsequent mitochondrial membrane depolarization (Thushara et al 2015). Of note, two of increasingly used supplements, resveratrol and melatonin, were reported to also induce platelet apoptosis via Bax translocation into mitochondria, increase cytochrome c release and caspase-3 activation (Thushara et al 2015).…”
Section: Platelet Mitochondrial Function In Cancermentioning
confidence: 99%
“…27) Platelet apoptosis produces microparticles, in which a variety of constituents are enclosed, including transcription factors and mRNA. 25,28,29) Among the microparticles in human blood, platelet-derived microparticles (0.1-1 µm) are the most numerous (approx. 240 × 10 3 /mL), 30,31) although they are far fewer in number than platelets themselves.…”
Section: Current Understanding Of Plateletsmentioning
confidence: 99%